Poverty Reduction Strategies - Kircher, Philipp (2002)
Poverty remains one of the greatest problems of our time, causing starvation and humiliation in poor countries and contributing to problems of conflict, migration and environmental degradation effecting also richer countries. This study provides a systematical analysis of today’s donor strategies for development cooperation, which unite around the goal of poverty reduction. The most recent strategies of the World Bank and the German, British and Swedish official development agencies are compared and evaluated. Their broad consensus on goals and conceptual elements is comprehensively presented. Differences in accentuations regarding beneficiaries and implementation methods are highlighted. An empirical study of the poverty focus in project evaluations of the German Financial Cooperation rounds off the analysis by exemplarily pointing at the practical implications of the new strategies.